Multivariate analysis for resolving interactions of carbidopa with dsDNA at a fullerene-C60/GCE - Gholivand, Mohammad Bagher (2014)
For the first time, interactions of carbidopa (CD) with double-stranded calf thymus DNA (dsDNA) in a phosphate buffered solution (PBS, 0.05 M, pH = 4.0) at a fullerene-C60/glassy carbon electrode (FLR/GCE) has been studied by cyclic voltammetry (CV), linear sweep voltammetry (LSV), and square wave voltammetry (SWV). The interaction of CD with dsDNA was also monitored using fluorescence (F) and UVvis spectroscopic techniques. New information was obtained when a row- and column-wise augmented matrix consisting of SWV, LSV, F and UVvis data was resolved using multivariate curve resolution-alternating least squares (MCR-ALS) as a powerful chemometric tool. Pure electrochemical and spectroscopic signals of CD, dsDNA and dsDNA-CD2 complex, and their concentration profiles were then successfully resolved. Molecular docking studies confirmed that the binding of CD with dsDNA shows minor groove binding mode which was in accordance with experimental results. Under optimized conditions, the SWV responses were linearly related to dsDNA concentration between 0.1 and 25.0 nM and a limit of detection (LOD) of 0.03 nM was calculated (3Sb/b = 3). Moreover, the modified electrode exhibited long term stability, good repeatability, and reproducibility, and high sensitivity and selectivity towards dsDNA determination in human serum samples, demonstrating its feasibility towards dsDNA sensing.